Optimizing decision-making in digital business processes through artificial intelligence - Rania Rofiatul Imama; Shinta Hanum Indah Pratiwi; Tri Rizki (Interdisiplinary Journal of Pedagogy and Research in Media Technology, 2025)
Background: The rapid growth of digital business environments has increased the complexity of managerial decision-making due to the proliferation of large-scale, dynamic, and heterogeneous data. Traditional intuition-based decision-making approaches are increasingly insufficient to address uncertainty and complexity in digital business processes, leading organizations to adopt Artificial Intelligence (AI) as a strategic decision-support mechanism.Aims: This study aims to examine the role of Artificial Intelligence in optimizing decision-making within digital business processes by synthesizing existing literature to identify key patterns, themes, and contributions of AI across various business contexts.Methods: This study employs a literature review approach using a thematic synthesis of relevant academic publications. Peer-reviewed articles, review papers, and conceptual studies related to Artificial Intelligence and decision-making in digital business were systematically analyzed to identify recurring themes, research trends, and decision-making implications.Result: The results indicate that Artificial Intelligence functions as an active, data-driven decision-support mechanism that enhances the accuracy, consistency, and timeliness of decision-making in digital business processes. The findings reveal that AI supports decision-making across multiple contexts, including management information systems, small and medium-sized enterprises, innovation and marketing activities, and the financial sector, by enabling predictive analytics, reducing cognitive limitations, and improving evidence-based managerial decisions.Conclusion: This study concludes that the optimization of decision-making in digital business processes depends not only on the adoption of Artificial Intelligence technologies but also on their effective integration into organizational decision structures and human judgment. Artificial Intelligence plays a central role in strengthening data-driven, evidence-based decision-making and contributes to improved organizational adaptability and competitiveness in the digital era.